Nurses’ Job satisfaction and Burnout : Is there a Connection? - Rosales, Rheajane Aguilar; Rosales, Gilbey Lao; Labrague, Leodoro Jabien (International Journal of Advanced Nursing Studies, 2013)
Burnout associated with stress has been documented in healthcare professionals including nurses and is considered as one of the potential hazards occurring among individuals who do “people work” (Cherniss, 1980). This study aimed to determine the level of job satisfaction and burnout among nurses in three government hospitals of Samar, Philippines. Descriptive-correlational method of research was utilized to all (48) regular nurses in three Government Hospitals of Western Samar, Philippines. Job Satisfaction Survey (JSS) by Pul E. Spector, and Maslach Burnout Inventory (MBI) by Cristina Maslach were administered to the respondents. Findings indicated that respondents experienced a moderate level of burnout and claimed to be slightly unsatisfied with their job. The highest scored subscale on the JSS was the Nature of the Work (m = 3.97) while the lowest scored subscale was the Fringe Benefit (m = 2.40). Findings revealed that the highest ranked subscale on the MBI was the Emotional Exhaustion (m = 3.28). On the other hand, Depersonalization subscale was the lowest scored subscale with a mean of 2.74. Analyses also showed that there is a significant relationship between the respondent’s level of burnout and their level of Job Satisfaction. The result showed a statistically significant relationship between the nurse-respondents level of burnout and their level of job satisfaction which may affect on the quality of care given to their patients. Thus, proper measures must be made to prevent and manage nurses’ burnout. Furthermore, it proposed a job enrichment program to increase the level of job satisfaction and prevent burnout.